Предмет: Алгебра,
автор: SFPD1
найдите значение выражения (6m-n)(6m+n)-(12m-5n)(3m+n) при m=-8/9 n=3/4
Ответы
Автор ответа:
11
(6m - n)(6m + n) - (12m - 5n)(3m + n) =
= (6m)² - n² - (36m² + 12mn -15mn -5n²) =
= 36m² - n² - 36m² +3mn + 5n² =
= (36m² - 36m²) + 3mn + (5n² - n²) =
=3mn + 4n² = n*( 3m + 4n )
= (6m)² - n² - (36m² + 12mn -15mn -5n²) =
= 36m² - n² - 36m² +3mn + 5n² =
= (36m² - 36m²) + 3mn + (5n² - n²) =
=3mn + 4n² = n*( 3m + 4n )
Похожие вопросы
Предмет: Математика,
автор: sanekrussak1992
Предмет: Геометрия,
автор: maervladimir41
Предмет: Математика,
автор: girkavadim
Предмет: Геометрия,
автор: FreemanTV
Предмет: История,
автор: LubashaOskolkova